Applied Social Sciences : Communication Studies. - Clitan, Gheorghe (Cambridge Scholars Publishing, 2013)
This book, Applied Social Sciences: Communication Studies, is a collection of essays specific to the field of Verbal and Non-verbal Communication. It contains essays on the role of communication in the academic library (interculturality), IT (collaborative web, digitalisation), literary fiction (folktale, Romanian drama), management (conflict management, election campaign discourse, public relations, terrorism risk), marketing (advertising, brand, cultural events), mass-media (censorship, glo ...